DIGITALIZATION OF MSME FINANCE AS AN EFFORT to IMPROVE BUSINESS EFFICIENCY AND TRANSPARENCY IN LAMPUPOK VILLAGE, INDRAPURI SUBDISTRICT, ACEH BESAR - Nasution, Emmi Suryani; Syamsidar, Syamsidar; Lastri, Surna; Purnamasari, Desi (Universitas Muhammadiyah Aceh, 2025)
Community Service Activities (PKM) carried out in Lampupok Village, Indrapuri District, Aceh Besar aims to provide understanding and knowledge to Micro, Small and Medium Enterprises (MSMEs) in the Village regarding the importance of good financial records and the use of digital technology in financial management so as to increase efficiency and transparency regarding how much funds are used and the actual financial position, both profits and losses obtained. This activity involves MSME business actors, most of whom are Acehnese snack businesses, on average these business actors do not have much experience because they are still new to the MSME business world. The activity method is carried out using interactive lectures to provide an explanation of the importance of financial recording for business and introduce financial applications through technology. Discussion sessions are also held for participants to provide an opportunity to ask questions and exchange experiences and solutions as one way to solve obstacles faced in financial management.Based on the evaluation results, this activity can improve the understanding of participants by showing high interest in the use of digital technology in their financial records.In every activity there must be challenges, as well as in this activity such as limited knowledge and access to technology, this activity also provides a positive contribution in supporting the digital transformation of MSMEs. Suggestions for future activities to create training using more interactive digital accounting applications, so that participants can more easily implement the knowledge gained in their businesses. Keywords: MSMEs, financial records, digitalization